Tecnologías de la información y comunicación y su utilización en la educación secundaria: Caso Federico Froebel - Guananga Barragán, Axcel Jorge (2020)
This research addressed the issue of the implementation of information and communication technologies in the 3rd Baccalaureate of the Federico Froebel Unit of the Babahoyo city, province of Los Ríos, because the study modality changed from being face-to-face to being completely virtual, by provision of the government to avoid contagion in times of a Covid-19 pandemic. The main objective of the case study was to identify the advantages and disadvantages that occurred in the teaching-learning process in the aforementioned course. The development of the theoretical framework is based on bibliographic sources of the topic of interest. A mixed approach methodology was proposed, with two interviews to teachers, respectively to Ab. Fran Braña Fernández Msc, and Professor Hercilia Jaime Morales and a survey applied to students, and additionally the observation of virtual classes, which allowed to know first-hand information. According to the analytical-synthetic method carried out, it is concluded that one of the most important advantages is that thanks to these technologies the corresponding teaching period has been met. On the contrary, the disadvantage that has arisen is under direct contact of teachers with students, especially with those who do not actively participate. And the problems that the campus has solved, for their teachers, is the connection of devices to the Internet.